COLLECTION OF SHORT STORIES KONVENSI BY A. MUSTOFA BISRI: STUDY OF STILISTICS AND ITS UTILIZATION IN LEARNING INDONESIAN LANGUAGE IN SENIOR HIGH SCHOOL - Mujadidi, Muhammad Sibghotallah; Kasa, Deeana; Setiawan, Budhi; Chaesar, Ari Suryawati Secio (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
As an artist, humanist, and religious leader, A. Mustofa Bisri's literary works have a distinctive character and contain a lot of educational value. This study aims to describe the use of diction, imagery, and style of language in A. Mustofa Bisri's short story collection Konvensi, as well as the use of the results of this study in learning Indonesian in high school. This research method is descriptive qualitative with a stylistic approach. The data sources are 15 short stories and 5 high school teachers in Surakarta. Data collection was carried out by document analysis and interviews. Data validity test was carried out using theoretical triangulation techniques and data source triangulation. Data analysis was carried out using a flowing model. The results of this study are as follows: (1) in the collection of short stories Konvensi there are 7 types of diction and concrete words dominate; (2) there are 7 types of images and the one that appears most often is the image of feelings; (3) there are 23 types of figurative language and the dominant one is the repetition style; and (4) the results of the analysis of the use of diction, imagery, and relevant language styles are utilized in learning to read and write short story texts in Indonesian subjects for grade 11 high school because they contain a variety of writing styles so as to enrich students' insights in literary literacy.